Acute myocardial injury and infarction in patients under 45 years old - a single centre experience. (2nd May 2022) - Cabral, M; Carvalho, MF; Goncalves, C; Santos, B; Morais, J
Abstract: Funding Acknowledgements: Type of funding sources: None. Acute myocardial injury and infarction is vastly described in patients over 45 years of age. However, the higher incidence of coronary artery disease (CAD) in young patients in recent decades has led to a concomitant increase in the importance of excluding coronary artery disease in this group. The aim of this study was to analyse the prognosis in young patients with acute myocardial injury and infarction. Additionally, we intend to evaluate the clinical features and angiographic profile. We retrospectively analysed all patients under 45 years of age with acute chest pain and elevated troponin who underwent coronary angiography in our department from January 2017 to April 2021. Patient selection and information collection were obtained through medical records. The patients were categorized into three groups, based on discharge diagnosis: group 1 for ST-segment elevation myocardial infarction (STEMI) patients, group 2 for non-ST-segment elevation myocardial infarction (NSTEMI) patients and group 3 for patients with angiographically normal coronary arteries. Outcomes were left ventricular dysfunction, assessed by left ventricular ejection fraction (LVEF) in transthoracic echocardiography; the occurrence of electrical complication during hospitalization, including sustained ventricular tachycardia, ventricular fibrillation or cardiorespiratory arrest; and in-hospital mortality. Group comparisons were performed. A p-value less than 0.05 was considered significant. Statistical analysis was performed using SPSS software v.25.0. One hundred twenty-one patients were analysed: 59 (48.8%) in group 1, 28 (23.1%) in group 2 and 34 (28.1%) in group 3. Table 1 describes the main baseline characteristics. There was a significant difference between the groups for smoking (p-value = 0.03), more prevalent in group 1 and less prevalent in group 3. Regarding outcomes, there was a significant difference for left ventricular dysfunction at discharge, with a mean LVEF of 50% in group 1, 53% in group 2, and 58% in group 3 (p-value < 0.01). The existence of electrical complications was similar for the three groups (p-value = 0.99), and all patients were discharged alive. In conclusion, young patients with acute myocardial injury and infarction have a similar clinical history, with the exception of smoking in STEMI patients. There was a higher prevalence of left ventricular dysfunction in patients with STEMI, similar to that observed in older patients. A multicentric analysis, as well as a long-term follow-up, would be interesting to confirm these results.